A methodology to assist project-based organisations to utilise and develop project management capability as a strategic asset to increase competitive advantage - Nel, Coenraad Josephus (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.